ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA PESERTA CALISTUNG SMP NEGERI 8 JEMBER - Firda, Jazilatul; Setiawani, Susi; Murtikusuma, Randi Pratama (Kadikma, 2019)
This study aims to describe the mathematical communication skills of junior high school students who experience deficiencies in reading writing, and counting (calistung). Mathematical communication ability consists of mathematical communication skills in verbal and in writing. The subjects of this study were 4 students in the calistung class. The method of data collection is through tests, interviews, and observations. Based on the results of the analysis, the mathematical communication skills of the calistung participants (reading, writing and counting) were in the range of the lowest three levels. Student 1 (S1) is at level 2 which is good enough. Student 2 (S2) mathematical communication skills are at level 2 which is quite good. Student 3 (S3) mathematical communication skills are at level 2 which is quite good. The mathematical communication ability of Student 4 (S4) is at level 1 which can be said to be of poor ability because it only fulfills 9 indicators out of all 32 indicators. Keywords: communication skills, mathematical communication skills, mathematical problem solving.